Localized mutations in the gene encoding the cytoskeletal protein filamin A cause diverse malformations in humans. - Robertson, S; Twigg, SR; Sutherland-Smith, A; Biancalana, V; Gorlin, R; Horn, D; Kenwrick, S; Kim, C; Morava, E; Newbury-Ecob, R; Orstavik, K; Quarrell, O; et al. (2003)
Remodeling of the cytoskeleton is central to the modulation of cell shape and migration. Filamin A, encoded by the gene FLNA, is a widely expressed protein that regulates re-organization of the actin cytoskeleton by interacting with integrins, transmembrane receptor complexes and second messengers. We identified localized mutations in FLNA that conserve the reading frame and lead to a broad range of congenital malformations, affecting craniofacial structures, skeleton, brain, viscera and urogenital tract, in four X-linked human disorders: otopalatodigital syndrome types 1 (OPD1; OMIM 311300) and 2 (OPD2; OMIM 304120), frontometaphyseal dysplasia (FMD; OMIM 305620) and Melnick-Needles syndrome (MNS; OMIM 309350). Several mutations are recurrent, and all are clustered into four regions of the gene: the actin-binding domain and rod domain repeats 3, 10 and 14/15. Our findings contrast with previous observations that loss of function of FLNA is embryonic lethal in males but manifests in females as a localized neuronal migration disorder, called periventricular nodular heterotopia (PVNH; refs. 3-6). The patterns of mutation, X-chromosome inactivation and phenotypic manifestations in the newly described mutations indicate that they have gain-of-function effects, implicating filamin A in signaling pathways that mediate organogenesis in multiple systems during embryonic development.